Kepemimpinan Para Rasul dan Relevansinya Bagi Pemimpin Gereja di Era Revolusi Industri 4.0 - Eli Wilson Ipaq; Hengki Wijaya (Sekolah Tinggi Teologi Jaffray Jakarta, 2019)
The article “Leadership of the Apostles and Their Relevance for Church Leaders in the Industrial Revolution Era 4.0,” aims to explain the characteristics of the leadership of the Apostles based on Acts, and their relevance to church leaders today. Precisely how the values ​​of the leaders of the Apostles were integrated into the era of the industrial revolution 4.0. Thus, the situation of the industrial revolution era 4.0 was influenced by servant, spiritual, and transformative leadership. This leadership is reflected in the life of Jesus. This leadership continued to the apostles and disciples of Christ.